Resíduo de acerola em dietas para coelhos na fase de crescimento - Tavares, Leila Maria de Sousa (2021)
Two assays were carried out to determine the nutritional and energy value of acerola residue and to evaluate the dietary inclusion of this feedstuff on animal performance, digestibility of diets, carcass traits, meat quality, biochemical parameters, and economic viability of growing rabbits. For assay 1, 36 rabbits (male and female) were assigned to three treatments: reference diet, T15 and T30 diets (test diets with replacement of 15 and 30% of the reference diet with acerola residue, respectively). Acerola residue contained 91.00% dry matter, 10.02% crude protein, 54.79% acid detergent fiber, and 1295.40 kcal DE/kg. For assay 2, 120 rabbits (60 male and 60 female) were assigned to a 5x2 factorial randomized block design, with 5 inclusion levels of acerola residue (0, 8, 16, 24 and 32%) and two sexes (male and female). The inclusion of acerola residue from 16% increased the feed intake and feed conversion without effects on weight gain and carcass traits up to the level of 32%. The dietary inclusion of acerola residue did not influence the triglycerides, total cholesterol, HDL and LDL cholesterol of the animals. The dietary inclusion of acerola residue linearly increased the antioxidant activity and potential of blood. The acerola residue supply reduced cooking losses, with higher levels of phenolic compounds observed from the inclusion level of 16%. The inclusion of acerola residue promoted a linear decrease in the average feed cost per kilogram bodyweight and cost index, and positively affected the economic efficiency. The acerola residue can be added to growing rabbit diets up to the level of 16%.